KickResearch module: research proposal made easy! / Azlyn Ahmad Zawawi ... [et al.] - Ahmad Zawawi, Azlyn; Azizan, Intan Syahriza; Mohd Yusof, Noorlailahusna; Ismail, Junaida; Ahmad, Nor Ardyanti (Universiti Teknologi MARA, Kedah, 2023)
The KickResearch Module is a structured and efficient research tool designed to facilitate comprehensive research projects for novice researchers. Its unique, standardized template allows researchers to follow a systematic and structured writing process, thereby streamlining research production and enhancing output quality. The module's distinctive feature is its ability to provide a practical solution for individuals lacking the resources or expertise to conduct high-quality research. KickResearch's potential for commercialization is noteworthy as it can be applied to various research topics and industries. Its practicality and uniqueness are grounded in its 5-step research process, which can be executed within a 6-month timeline.The steps include refining the research topic, followed by a comprehensive literature reviewto identify existing research and knowledge gaps. The steps also involve the planning of the data collection process, the identification of stakeholders, and the drafting of the initial report.This structured process provides a clear and systematic path for researchers, enabling them to efficiently produce high-quality research output. The KickResearch Module package includesa user-friendly log sheet that consists of a 5-step research process, a systematic reading template, and an effective writing guide. These templates can be easily modified to suit the researcher's specific research needs and study specifications. The KickResearch Moduleoffers guidance and support throughout the entire research process, making it an essential toolfor anyone seeking to conduct a comprehensive research project. Its practicality and uniqueness make it a valuable asset for researchers across different industries and disciplines.